ASSESSMENT OF AWARENESS ABOUT ORAL HYGIENE IN CHILDREN OF SCHOOL AGE: A CROSS-SECTIONAL STUDY - Nadezhda Mitova; Milena Georgieva; Peter Bakardjiev (Journal of IMAB)
Introduction: Hearing impairments are often associated with communication difficulties, which can Introduction: Education about oral hygiene during childhood is essential for establishing habits that promote lifelong oral health. Children are more likely to practice good oral hygiene as they understand the long-term benefits of maintaining their oral health. Aim: To assess the level of oral hygiene awareness among school-age children (ages 6–12), including knowledge about brushing techniques, oral hygiene products, and the importance of maintaining good oral health. Materials and method: This study includes 287 school-aged children (6 to 12 years) who responded positively to the question of whether they had received training or knowledge on oral health promotion at least once prior to the study. All participants completed a questionnaire regarding their awareness of oral hygiene. Results: According to the distribution of the source of oral health education, most children (79,8 %) reported receiving their knowledge from parents, teachers, and dentists. About 20,2 % of children are educated about oral health through various digital sources. The data show that statistically, the most of children use a manual toothbrush (56,1 %), while a smaller number use an electric – 35,5% or ultrasonic one – 8,4 %. The children studied show stable knowledge regarding the necessary frequency of tooth brushing, with the majority (85,7%) reporting that they brush their teeth twice a day. Conclusion: The implementation of informational and educational oral health programs in schools and within families plays a crucial role in improving children's health literacy, enhancing their oral hygiene practices, and reducing the incidence and prevention of oral diseases during childhood.